Phép thử lý thuyết tốc độ phản ứng đơn phân tử trong phản ứng nhiệt - Quý, Trầnh Vĩnh; Độ, Nguyễn Đình (Vietnam Journal of Chemistry, 2014)
The limiting high-pressure unimolecular rate constant k¥ in thermal systems can be considered as the Laplace transform of the detailed rate constant, or specific dissociation probability, k(E) (E = internal energy). If k¥ is known from experiment as a function of temperature in the form k¥=A¥exp(-E¥/kT), k(E) can be obtained by inversion. Using one actual examples, the inversion procedure is exploited to show that k¥ contains sufficient information for a test of unimolecular rate theory that requires only the knowledge of the molecular properties of the reactant but not those of the transition state. Since there are no parameters to adjust, this test, in a thermal system, is therefore more significant than the more usual speculative curve-fitting.